KONTRIBUSI ETOS KERJA DAN PELAKSANAAN SUPERVISI TERHADAP KINERJA GURU PADA SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 1 SUMATERA BARAT - Ilmiyati Rahmy Jasril (Jurnal Teknologi Informasi dan Pendidikan, 2016)
This study aims to reveal contribution of work ethic and implementation of supervision toward the teacher’s performance both partially and simultaneously. This was a correlational study. The population and sample of this study was teachers of vocational high school (SMK) Negeri 1 West Sumatera. The sample was selected by using stratified proportional random sampling techniques. The data were collected by using questionnaire with Likert-scale model. The data were analysed using correlation and multiple regression techniques with stepwise method. The results of this study indicate that there was a significant contribution work ethic and implementation of supervision toward the teacher’s performance of vocational high school (SMK) Negeri 1 West Sumatera both partially and simultaneously.The findings and recommendations of the study are useful to improvement of teachers’ performance